2014
DOI: 10.1039/c3ob42277a
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and biological evaluation of mycobacterial p-hydroxybenzoic acid derivatives (p-HBADs)

Abstract: Synthetic p-hydroxybenzoic acid derivatives (p-HBADs) from Mycobacterium tuberculosis have the ability to suppress host immune response in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 44 publications
(73 reference statements)
3
30
0
Order By: Relevance
“…These results are in agreement with our earlier work on synthetic analogues from M. leprae and M. bovis 17 and, taken together, demonstrate that the glycan portion of PGLs alone can inhibit release of the evaluated cytokines and NO. This conclusion is further supported by a recent investigation on p ‐HBAD‐I and p ‐HBAD‐II 19. In this study, Scanlan and co‐workers showed that p ‐HBAD‐I and an analogue lacking the methyl group on the rhamnose moiety exhibit an inhibitory effect on the release of some cytokines, in particular TNF‐α and IL‐12p40.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results are in agreement with our earlier work on synthetic analogues from M. leprae and M. bovis 17 and, taken together, demonstrate that the glycan portion of PGLs alone can inhibit release of the evaluated cytokines and NO. This conclusion is further supported by a recent investigation on p ‐HBAD‐I and p ‐HBAD‐II 19. In this study, Scanlan and co‐workers showed that p ‐HBAD‐I and an analogue lacking the methyl group on the rhamnose moiety exhibit an inhibitory effect on the release of some cytokines, in particular TNF‐α and IL‐12p40.…”
Section: Discussionsupporting
confidence: 76%
“…We report here the synthesis of a similar panel of analogues of known PGLs from M. tuberculosis ( 1 – 3 , Scheme ),7, 18 and an evaluation of their ability to modulate the production of various cytokines and nitric oxide (NO). This work complements a very recent study by Scanlan and co‐workers on p ‐HBAD‐I and p ‐HBAD‐II obtained by chemical synthesis 19…”
Section: Introductionsupporting
confidence: 82%
“… 47 Moreover, chemically synthesized p -HBAD-I and II have been shown to suppress T-cell proliferation and activation, and block the production of pro-inflammatory cytokines by irradiated M. tb -stimulated murine bone marrow-derived macrophages in vitro. 48 Given the overwhelming evidence that many individual mycobacterial glycolipids and glycans individually display immunomodulatory properties, their overall effect on the host immune system when immunostimulatory mycobacterial Ags are also present, remain to be ascertained and warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium tuberculosis secretes a complex variety of glycosylated compounds present in the cell wall during infection which acts as immunomodulatory molecules. p-hydroxybenzoic acid derivatives (p-HBADs) are synthesized by Mycobacterium tuberculosis to inhibit the production of inflammatory cytokines, particularly interferon-γ (IFNγ) by T-cells [18]. Mycobacterium tuberculosis controls the host cell machinery through its transcription factor sigma-E involved in the modulation of the host inflammatory response against the pathogen.…”
Section: Inhibition Of Inflammation As a Survival Strategy For Mycobamentioning
confidence: 99%